Perbandingan Indonesia dan Nepal Dalam Kondisi Geografis, Distribusi Layanan Publik dan Perkembangan Infrastruktur - Bagus Prasetiyono; Galih Putra Kusuma; Allena Jasmine Putri Huda; Moh. Musleh (Policy and Maritime Review, 2025)
Indonesia and Nepal are developing countries in Asia with contrasting geographical characteristics that influence infrastructure development and public service distribution. Indonesia is an archipelagic country with vast maritime areas and dispersed islands, while Nepal is a landlocked mountainous country dominated by the Himalayan region. These geographical differences create distinct challenges in ensuring equitable infrastructure development and public service delivery. This study aims to analyze the relationship between geographical conditions, infrastructure development, and public service distribution in Indonesia and Nepal through a comparative literature review. The study employs the perspective of territorial governance, which emphasizes that public policies and infrastructure strategies should be adapted to regional spatial characteristics, demographic conditions, natural resources, and disaster risks. Data were collected from academic literature, international reports, and previous studies concerning infrastructure development and public service governance in both countries. The findings indicate that geographical conditions significantly affect infrastructure accessibility and the distribution of public services. In Indonesia, the archipelagic structure increases transportation and connectivity costs across islands, while in Nepal, mountainous terrain constrains road construction and regional accessibility. Both countries have implemented decentralized governance approaches to address these challenges, supported by local government initiatives and development partners. However, disparities in service accessibility remain evident, particularly in remote and geographically isolated areas. This study concludes that geography is a critical determinant of infrastructure development and public service distribution. Effective territorial governance, adaptive infrastructure planning, and geographically sensitive public policies are essential to reducing regional disparities and improving public service accessibility in developing countries.